PENERAPAN MODEL LEARNING TOGETHER UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR SISWA - Zulkipli (DIADIK, 2022)
This research was conducted with the aim to find out 1) The application of the Learning Together Model can increase student Cooperationlearning Islam Religion Education subjects, 2) The application of the Learning Together model can improve student learning achievement in Islam Religion Education subjects in Students and 3) The effectiveness of the application model Learning Together in improving student learning achievement in learning Islam Religion Education subjects Class X in SMA Negeri 1 Kikim TimurLahat. This study used Class X IPS1 as much 25 subjects in PTK research, Class X IPS2 as much 20 subject in experimental class research, and Class X IPS3 as much 20 people in control class research.Data collection techniques in this study used observation and tests. The results of this study indicate that The application of Learning Togethermodel can increase studentcooperation in Islam Religion Education subjects.The application of Learning Together model can improve student learning achievement in Islam Religion Education subjects.The application of a Learning Together model can effectively improve student learning achievement in Islam Religion Education subjects class X in SMA Negeri 1 Kikim TimurLahat.